Analisis Persepsi Konsumen terhadap Citra Merek dan Harga dalam Keputusan Pembelian Hand and Body Lotion Vaseline pada Mahasiswa - Annas Wahyu Hertanti; Giyana Giyana (Universitas Kristen Indonesia Toraja, 2025)
In the marketing domain, brand image and price are pivotal factors influencing consumer purchasing decisions. This study aims to analyze the perceptions of university students regarding the balance between brand image and price in purchasing Vaseline hand and body lotion. Using a qualitative approach, data were gathered through a systematic literature review and secondary sources, focusing on consumer behavior and skincare product preferences. The findings reveal that students perceive Vaseline as a high-quality brand offering clear skincare benefits. However, price remains a significant determinant due to the limited budgets typical of this demographic. This research contributes to theoretical understanding and provides practical insights for developing marketing strategies targeting university students by aligning brand communication and pricing strategies with their needs and preferences.